Early Childhood Motor Development Through Traditional Games in Children Aged 5-6 Years at Erwita Educare Center Kindergarten - Gustina, Fatma (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
The study aims to determine the motor development of children aged 5-6 know in kindergarten Erwita Educare Center Kec. Medan at a glance, Setia Budi. This research method is qualitative, which uses observation instruments, interviews, and documentation. Analysis of the data used is data collection, data reduction, data display and draw conclusions. The research findings point to (1) the development of children's motor skills through well-developed traditional games, (2) the teacher with his creativity developing gross motor and fine motor skills with some traditional games (3) there are some traditional games that develop fine and gross motor skills for example traditional games that can develop gross motor skills such as playing squatting, dampug, galasin, jumping rope, and traditional games that can develop fine motor skills of children are congklak, marbles, bekel. The obstacle in children's motor development is that children rarely attend school and children who are introverted and moody.